Analisis Peningkatan Kesejahteraan Masyarakat Melalui Usaha Mikro Kecil Dan Menengah Di Kecamatan Pengabuan Kabupaten Tanjung Jabung Barat - Agustina Mutia; Muhammad Orinaldi; M Hasan (Lembaga Pengembangan Kinerja Dosen, 2023)
The purpose of conducting this research is to find out how the development of MSMEs in Pengabuan District, West Tanjung Jabung Regency and to find out what are the obstacles that make MSMEs in Pengabuan District, Tanjung Jabung Barat Regency slow to develop and to find out how the government contributes in advancing MSMEs to improve people's welfare in the District. The incineration of West Tanjung Jabung Regency. Fahrudin's Community Welfare Theory. How does a person or individual meet the basic needs of his life, as well as how does one support the opportunity to continue his education and have a better job to support his quality of life. The results of this study indicate that in improving the welfare of the people in Pengabuan District, Tanjung Jabung Barat Regency, it is seen by indicators of welfare, income, education and health. Of the 10 Respondents from Micro, Small and Medium Enterprises interviewed by researchers, many said that the purpose of doing this MSME business was to help the economy in the family, as well as increase income for their husbands and to help meet their daily needs and fulfill their children's education. and health for their families. And in an effort to improve the welfare of business actors, it is hoped that the contribution from the relevant government will advance their business so that their business can develop much better than before.